Study of s-polarized photonic bandgap structure in three component optical fibonacci multilayers composed of nanoscale materials - Mishra R.K.; Pandey P.C. (My University, 2025)
In this communication dispersion relation, reflection and transmission coefficient for quasiperiodic optical multilayers arranged according to the three-component Fibonacci rule is derived using transfer matrix method. In this work Fibonacci multilayers using three different photonic band gap (PBG) materials is designed and its photonic band gap structure is presented. Also, a detailed calculation for allowed and forbidden frequency bands for s-polarized radiation of light incident on these structures at various angles is presented. It is demonstrated that in case of s-polarized mode of radiation, widening in the band gap and frequency shifts occur as one moves towards the higher frequency region, which shows that such a multilayer can be used as an efficient polarizer. The effect of an imaginary value for the propagation vector Q on the existence of forbidden photonic bands in these lattices is also studied. © 2009 Elsevier Ltd. All rights reserved.